The social construction of normalcy in post-Yolanda Tacloban City the role played by business establishments - de la Cruz, Judee Anne C.; Luquing, Amanda Claire G.; Magsoling, Therese Princess Gem B.; Ogario, Mer Inisa D.; Oquendo, Rene Alvin F. (2015)
Normalcy in the context of this study refers to the restoration of normal community activities that were disrupted by disaster impacts. Consequently, the researchers sought to uncover how the reappearance of business establishments shaped the social construction of normalcy in post-Yolanda, Tacloban City.
This research uses social constructivism as a framework which highlights the importance of people's thoughts, ideas, actions, behaviour and language. In line with this, the researchers used peoples' patronage toward business establishments as a gauge in identifying whether there is an association of normalcy to that of the establishment's reappearance after Super Typhoon Yolanda.
This study is a qualitative research and semi-structured interview were used to gather the necessary information. Interviews with business owners and representatives, market stall owners, government agencies, a local business organization, and with residents of Tacloban City were conducted. The researchers utilized thematic analysis in order to identify the relevant pieces of information from the data gathered.
A denaturalization of normalcy was observed wherein the notion of normalcy being seen as 'automatic', 'objective' and an absolute truth independent upon the interpretation of individuals is challenged. The data revealed that the absence and presence of business establishments did affect how people construct normalcy and were also suggestive of the mutual influence exerted by both establishments and individuals on each other as identities of both actors are mutually shaped by the interrelated interests, behavior and system of understanding. While it has been found that business establishments play an important part in restoring normalcy to areas hit by disasters, it is also apparent that the residents especially those who are not frequent patrons of such establishments have emphasized other factors that would make them feel more normal such as stable livelihood and permanent shelter.
Findings of the study showed that three main reasons were cited by the respondents consisting of representatives from business establishments such as supermarkets, restaurants and hard ware stores. These were the resumption of business for livelihood purposes, as a response to the demands of the customers and as a response to moral obligations.
Undergraduate thesis (B.A.S.S. Political Science)-- Univeristy of the Philippines, Tacloban.
Keywords: Typhoon Yolanda